Best defense - Mack, David, 1969- (Star trek, the original series., 2016)
Captain Kirk and his crew seek the stolen Transfer Key that opens a door to a parallel universe, but their hunt is cut short by Ambassador Sarek's plea for help from the long-awaited Klingon-Federation peace conference. The Enterprise crew soon become targets in a deadly crossfire, one whose outcome will decide the fate of two universes.